Effect of sub-optimal moisture levels on the quality of groundnut (Arachis hypogaea L.) during storage in triple-layer hermetic storage bags - Swathi, Y.; Rajanikanth, P.; Jella, Satya Narayana; Mangala, Uppala N.; Adithya, Guntha; Anilkumar, Vemula; Sudini, Hari Kishan (Frontiers in Sustainable Food Systems, 2024)
Storage is an important aspect of groundnut as the in-shell and shelled are prone to be infested by insects, pests and fungi. Among several storage pests, Groundnut bruchid, Caryedon serratus, causes serious losses. Farmers often resort to different management practices including hermetic storage to control it. Moisture content of the commodity plays an important role in insect infestation during storage. Drying to safe moisture levels before storage is a well-known fact in preventing the activity of various living organisms including storage pests. However, drying to low levels of moisture may not be economical to farmers as they may not have access to devices to check product moisture accurately. In this regard, we wanted to demonstrate the efficacy of triple-layer hermetic storage bags in preventing the damage caused by C. serratus when the groundnuts are stored with intermediate (10%) and high-levels (14%) of moisture vis-à-vis traditionally used bags such as polypropylene bags and jute bags. Groundnut pods with 10% moisture content and 14% moisture content were separately inoculated with adult bruchids and a toxigenic strain of Aspergillus flavus fungi inoculum before storing them for 6 months. Results from groundnut samples drawn on every two months’ intervals indicated that the groundnut pods stored in triple layer hermetic bags were completely free from infestation by C. serratus by recording zero number of egg laying, numbers of pupae, adult emergence, per cent loss and per cent damage up to six months’ storage period by creating low oxygen (hypoxia) and high carbondioxide (hypercarbia) conditions. Results also indicate no loss in pod weight stored in triple layer bags but little reduction in germination percentage was recorded which was due to slight increase in fungal activity, but the reduction was significantly less in triple layer plastic bags when compared to other bag types. Similarly biochemical constituents such as oil and protein contents were slightly reduced in triple layer plastic bags when pods were stored at 10% moisture level, but higher reduction was observed at 14% moisture level. However, the reduction was very high and significant in other bag types both at 10 and 14% moisture levels.